Moodivate: A self-help behavioral activation mobile app for utilization in primary care—Development and clinical considerations. (March 2017) - Dahne, Jennifer; Lejuez, CW; Kustanowitz, Jacob; Felton, Julia W; Diaz, Vanessa A; Player, Marty S; Carpenter, Matthew J
Depressive symptoms are highly prevalent and are associated with considerable functional impairment, significant public health costs, and heightened mortality risk. Individuals experiencing impairment due to depressive symptomatology are most likely to report their symptoms to a primary care provider. As such, national guidelines highlight the need to assess and effectively treat depression via primary care. Despite these guidelines, the dissemination of evidence-based psychotherapy via primary care is limited, likely due to both provider- and patient-level treatment barriers. Mobile health (mHealth) technologies are promising for addressing these barriers and for promoting uptake of evidence-based depression treatment. Among evidence-based psychotherapies for depression, brief Behavioral Activation Treatment for Depression (BATD) has shown great promise and is particularly amenable to mHealth delivery. Herein, we discuss the development of a BATD mobile application, Moodivate, that was developed in order to disseminate BATD via primary care. This paper focuses on description of (1) rationale for Moodivate treatment development, (2) Moodivate treatment components, (3) ongoing clinical trial evaluation of Moodivate, and (4) clinical considerations for incorporating Moodivate into clinical practice.